Toxicity of Ceremai (Phyllanthus Acidus) and Zodia (Evodia Suaveolens) Leaf Extracts on Mortality of Aedes Aegypti Larvae - Imtiyaz, Andi Hilman; Armiyanti, Yunita; Ulfa, Evi Umayah; Rohmah, Etik Ainun (Faculty of Medicine, Universitas Jember, 2024)
Aedes aegypti is the vector that carries Dengue Hemorrhagic Fever (DHF). Various strategies have been implemented to control the spread of the Aedes aegypti, one of which is using temephos larvicide. The use of temephos causes Aedes aegypti resistance and environmental pollution. Therefore, it is necessary to develop a bio-larvicide using ceremai leaf (Phyllanthus acidus) and zodia leaf (Evodia suaveolens). This study aimed to determine the toxicity of ceremai leaf and zodia leaf extracts on the mortality of Aedes aegypti larvae. This type of research is a pure experiment using a Completely Randomized Design. The research sample was third instar Aedes aegypti larvae. There were 7 groups consisting of 1 negative control (aquadest and tween20), 1 positive control (temephos 0.008%) and 5 treatment groups (ceremai leaf extract and zodia leaf extract). Larval mortality data were observed after 24 hours of exposure. The results of the Kruskal Wallis test showed that there was a difference in mortality between groups with a value of p : 0.020 (p < 0.05). Zodia leaf extract at 0.2% has the highest toxicity to the mortality of Aedes aegypti larvae. The probit test results of zodia leaf extract showed LC50 and LC90 values of 0.075% and 0.121% within 24 hours of exposure. Zodia leaf ethanol extract has effectiveness as larvicide of Aedes aegypti. Keywords: Aedes aegypti, larvicide, extract, ceremai, zodia